Analysis of The Effect of Fin Thickness Variations on The Decrease in Motorcycle Radiator Temperature Using Computational Fluid Dynamic - Saripudin, Mochamad Malik Abdullah; Setiawan, Reza (TRANSMISI, 2025)
The radiator is an important component in a motorcycle cooling system that functions to control engine temperature. The design and thickness of the fins on the radiator play a key role in determining the efficiency of heat transfer and pressure drop in the system. This study analyzes the effect of variations in fin thickness (0.14 mm, 0.17 mm, and 0.19 mm) on radiator performance using the Computational Fluid Dynamics (CFD) method. Simulations were performed at air velocities of 16.7 m/s, 27.8 m/s, and 33.3 m/s, with ethylene glycol coolant at 373 K and ambient air at 300 K. The simulation results show that thinner fin thicknesses, such as 0.14 mm, are more effective in reducing the coolant outlet temperature, with the lowest temperature achieved being 306.091 K. However, thinner fins also produce higher air outlet temperatures. Conversely, a fin thickness of 0.19 mm shows lower heat transfer efficiency, indicated by a higher coolant outlet temperature. The 0.17 mm fin thickness provides the best balance between coolant temperature drop and air outlet temperature, making it the optimal choice for efficient radiator design. With the right radiator design, the efficiency of the cooling system can be improved, which in turn contributes to better engine performance and longer engine life